Implementation Barries and Service Outcome of Telehealth Information in the Health Services: A Systematic Review - Widiyono Widiyono; Sri Huning Anwariningsih; Atik Aryani; Ranti Ningsih Sumarni (STIKep PPNI Jawa Barat, 2026)
Background: Digital transformation in the field of health services is increasingly experiencing novelty that can support the services provided to the community Telehealth technology in the form of telemedicine is an effort to use information technology that can help patients, health workers and health institutions to share information easily, quickly and safely. Research related to telehealth (remote healthcare services) is crucial to optimize the potential of technology in healthcare systems, especially after the COVID-19 pandemic, which has accelerated digital adoption. In addition to the many benefits, telehealth programs must be faced with the readiness of human resources, financing, facilities and infrastructure as well as clear legal aspects. Aims: The purpose of this literature review is to describe the use of telemedicine in the health profession in improving professional health services. Methods: The research design uses Literature Review, based on a summary of several studies related to the research topic Telehealth approach used was a literature review. Articles on the use of Telehealth technology were searched using topics and keywords related to